IMPLEMENTATION OF THE 7 GREAT HABITS OF INDONESIAN CHILDREN (KAIH) PROGRAM IN SHAPING THE CHARACTER OF SIXTH-GRADE STUDENTS AT UPT SD NEGERI 141 INPRES PARAPPUNGANTA II, POLONGBANGKENG TIMUR DISTRICT, TAKALAR REGENCY - Mery Yunistira Basnyam (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study explores the implementation of the 7 Great Habits of Indonesian Children (KAIH) Program in shaping the character of sixth-grade students at UPT SD Negeri 141 Inpres Parappunganta II, Takalar Regency. Using a qualitative case study approach, the research was conducted over two months and involved sixth-grade students, teachers, and the school principal. Data were collected through participant observation, semi-structured in-depth interviews, and document analysis. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing and verification, with trustworthiness ensured through triangulation, member checking, and peer debriefing. The findings indicate that the implementation of the KAIH Program significantly improved students’ character, as shown by an increase in average behavioral scores from the “Sufficient” category to the “Very Good” category within one month. The program effectively fostered discipline, spirituality, independence, social responsibility, and healthy lifestyle habits. However, habits related to waking up early and sleeping early required continuous reinforcement due to external environmental influences. Key supporting factors included strong school leadership, teacher commitment, parental involvement, and student enthusiasm. The study concludes that the KAIH Program is an effective strategy for character education, provided that sustained collaboration among schools, families, and communities is maintained.